2016
DOI: 10.3389/fnins.2016.00568
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Mechanoreceptor Feedback from the Hand and Foot Can Modulate Muscle Sympathetic Nerve Activity

Abstract: Stimulation of high threshold mechanical nociceptors on the skin can modulate efferent sympathetic outflow. Whether low threshold mechanoreceptors from glabrous skin are similarly capable of modulating autonomic outflow is unclear. Therefore, the purpose of this study was to examine the effects of cutaneous afferent feedback from the hand palm and foot sole on efferent muscle sympathetic nerve activity (MSNA). Fifteen healthy young participants (9 male; 25 ± 3 years [range: 22–29]) underwent microneurographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…Presently, we found no additional increases or decreases of MSNA with tactile stimulation during hand grip. A previous study showed decreased MSNA with vibration alone (Strzalkowski et al 2016), but it seems that in our experiment, the overriding effect was an increase in MSNA due to the hand grip. However, MSNA was generally lower during vibration and was significantly lower than MSNA with concurrent warmth.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Presently, we found no additional increases or decreases of MSNA with tactile stimulation during hand grip. A previous study showed decreased MSNA with vibration alone (Strzalkowski et al 2016), but it seems that in our experiment, the overriding effect was an increase in MSNA due to the hand grip. However, MSNA was generally lower during vibration and was significantly lower than MSNA with concurrent warmth.…”
Section: Discussioncontrasting
confidence: 75%
“…Conversely, recording MSNA at sites local to the skin stimulation have found the opposite effect, where innocuous cold can increase MSNA (Ishida et al 2016), whereas skin warming can decrease it (Takahashi et al 2011), which was thought to be part of a local regulatory reflex. The activation of Aβ low-threshold mechanoreceptors via vibration can decrease MSNA (Strzalkowski et al 2016), as can transcutaneous electrical skin stimulation (Goswami et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanoreceptors transmit tactile and proprioceptive feedback via sensory nerves to the central nervous system. 42 Sensory feedback from the skin interacts with descending motor commands at the spinal cord which allows reflexive modulation of motor neuron excitability. 43 The density of mechanoreceptors on the plantar aspect of the foot appears to follow a proximal-distal and mediolateral gradient, that is, a higher density of mechanoreceptors towards the lateral edge of the foot, the metatarsals and digits.…”
Section: The Impact Of Footwear On Innate Impact Moderatingmentioning
confidence: 99%
“…Conversely, recording MSNA at sites local to the skin stimulation have found the opposite effect, where innocuous cold can increase MSNA, (Ishida et al 2016), whereas skin warming can decrease it (Takahashi et al 2011), which was thought to be part of a local regulatory reflex. The activation of Aβ lowthreshold mechanoreceptors via vibration can decrease MSNA (Strzalkowski et al 2016), as can transcutaneous electrical skin stimulation (Goswami et al 2012).…”
Section: Introductionmentioning
confidence: 99%